O processo de formação continuada e a pesquisa em educação especial na pós graduação stricto sensu: o caso do PPGEEDUC/UFES - Silva, Sinara Amorim da (2025)
This research has as its theme the “continuing teacher education from the perspective of special education”, understood from the assumptions of Saviani (2007, 2008, 2011, 2019) in the light of Historical-Critical Pedagogy (PHC), Freitas (2002), Gatti (2001, 2003, 2008) and Imbernón (2010), understanding training as a reflective practice that integrates experience, knowledge and social context. Considering the themes focused on special education, the study seeks to answer: How has the training received at Postgraduate Program in Teaching, K–12 Education, and Teacher Education at the Federal University of Espírito Santo, Alegre Campus, Brazil. and the research carried out in the area of special education impacted the professional daily lives of the program's graduates? The general objective is to analyze the effects of the training received at the Teaching Postgraduate Program at UFES and the research carried out in the area of special education on the professional daily lives of the program's graduates. To this end, the following specific objectives stand out: to analyze, through a documentary approach, the research developed in the area of special education at Teaching Postgraduate Program at UFES since its creation, highlighting the themes addressed and contributions to the field; to understand the perceptions of former master’s students about the contributions of the Program and research for their continuing education in the area of special education; to analyze the influence of the formative process on the professional performance of the graduates in their current practice, considering the educational context in which they are inserted. This is a case study developed in three stages: documentary analysis of 22 dissertations; application of a questionnaire to characterize the graduates; and conducting narrative interviews, following the topical life history model proposed by Schütze (apud Bauer; Gaskell, 2008, p. 90 et seq.) and adapted by Jovchelovitch and Bauer (2008). The analyses of the questionnaire and interviews were organized based on the articulation of the data from the interviews and questionnaires. We organized the data into categories that we renamed as follows: “Who are they and where are they?”, “What does the research say?”, and “Professional and academic paths”. The results of the documentary analysis indicate potential social, educational, and/or professional development contributions. The analysis of the questionnaire and interviews identified positive effects of the program, as well as the research, on the personal and professional trajectories of the graduates, in addition to the impact on knowledge enhancement, critical reflection, career progression, and salary improvements. Regarding the influence of the training process on professional performance, it is clear that the program’s training expanded the graduates’ capacity to work in different educational contexts. It also highlights that research and the entire training process are tools for social transformation, encouraging participation, responsibility, and collective engagement. Furthermore, the program has a strong social contribution